The psychosocial work environment of women construction workers: an integrative literature review - Williams, Thato Leslie-Ann (My University, 2022)
Background: There is an increase in the number of women in the construction industry, which was considered as a masculine trade for decades. This is prone to have a bearing on the psychosocial work environment of women employed in this male dominated field of work. Women face unique challenges as opposed to their male counterparts who are employed in the same trade. These challenges include discrimination, sexual harassment, overlooked for promotions and being office bound regardless of education. These challenges can impact the psychosocial work environment of women in the workplace, which can result in them opting to exit the industry. Aims and objectives: To gather and critically analyse scientific literature to describe the psychosocial work environment of women employees in the construction industry. Design: An integrative literature review using the Whittemore and Knafl (2005) framework’s stages was used. These stages included problem identification, literature search, data evaluation, data analysis and presentation of findings. Methods: A comprehensive literature search was performed using Asce Library, Emerald, Science Direct electronic databases and from reference list of included articles. The studies were in English, published between January 1993 to November 2018. A total of 3764 studies were retrieved from the search. The inclusion and exclusion criteria were applied, and 57 studies were eligible for abstract reading, which yielded 7 eligible studies that were used in the study. Results: Four themes that emerged include, less representation of women in the construction industry due to inability of retaining women. Discussion and conclusion: Discrimination due to the benevolent sexism that women face. Stressful work environment which is amplified for women as it affects work-life balance. Labour laws, they are implemented and hardly reviewed. Women are an un-tapped resource and by eradicating these challenges by interventions the industry can be inclusive.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Nursing to the Faculty of Health Sciences, University of the Witwatersrand, 2022
Keywords: Psychosocial work environment and women; Construction work